Effect of Pressure and Time on Scco2-Assisted Incorporation of Thymol into Ldpe-Based Nanocomposites for Active Food Packaging - Guarda-Moraga, A; Romero-Figueroa, J; Galotto-Lopez, M; Rojas-Sepulveda, A; Torres-Mediano, A; Villegas-Vallejos, C (Elsevier Ltd, 2018)
In this work, the scCO2-assisted incorporation of thymol in LDPE nanocomposites with different concentrations of an organo-modified montmorillonite (OM-MMT) nanoclay is proposed as the preparation method of an antimicrobial food packaging system. Mass transfer characterization of thymol, for both incorporation and release processes, as a function of the nanoclay content of the material and the CO2 pressure during the impregnation at 313 K was carried out as well as the structural characterization of the nanocomposites, which was developed for a better understanding of the impregnation and release processes. From the incorporation and release experiments and their theoretical analysis, it was obtained that the intercalated structure of the nanocomposite materials did not involve an additional resistance to the thymol incorporation in the polymer structure during the scCO2-assisted impregnation process. Nevertheless, the decrease of the diffusion coefficient of thymol in the nanocomposite, Deff, during the release process from the material to a food simulant was observed. Thus, the Deff associated to thymol uptake in the nanocomposite materials took values between 2.17×10-12 and 2.44×10-11 m2 s-1. Meanwhile, the Deff of thymol associated to its release from the nanocomposite took values between 7.0 and 9.0×10-14 m2 s-1. Finally, the developed nanocomposite materials showed a thymol concentration that allows a strong antibacterial activity against S. aureus and E. coli. © 2018 Elsevier Ltd. All rights reserved.